Applying the damage assessment for rapid response approach to the august 24 M6 event of the seismic sequence in central Italy (2016) - Petrovic, Bojana; Scaini, Chiara; Parolai, Stefano (Frontiers in Earth Science, 2022)
Seismic monitoring networks are increasingly being used in urban areas to record and locate earthquakes. Recordings in the proximity of buildings also allow assessing, as a first approximation, the expected building damage. The DARR method (Damage Assessment for Rapid Response) provides local-scale information on expected damage patterns. The potential of this approach is discussed here for the August 24 M6 event of the Central Italy seismic sequence (2016-2017). We focus only on the first event of the sequence because cumulative damage is outside the scope of this study. The earthquake recordings are available from two Italian monitoring networks: the Italian Accelerometric Archive (ITACA) and the OSS (Osservatorio Sismico delle Strutture), which collects data from monitored buildings and bridges in Italy. We selected three target areas (Amatrice, Norcia and Sulmona) characterized by different epicentral distances and building typologies, that suffered different levels of damage during the M6 event on August 24, 2016. Using recordings either in the free field or in the basement of buildings, the expected building drift and displacement are calculated with the DARR method. Using predefined damage thresholds from literature, the obtained results allow quantifying the expected damage for dominant building typologies in the surroundings of the recording sites. We investigate and discuss the potential use and applicability of the DARR method in different areas depending on the epicentral distance and building characteristics. The results indicate that the DARR approach is useful for supporting and improving rapid response activities after a seismic event.